Number of Seedlings per Clump and NPK fertilization Effect on Growth and Yield of Lowland Rice Based on The Leaf-Color Chart - H. Hairmaudiana; Marlina Mustafa*; Mustafa R; Musadia Afa (Agrotech Journal, 2023)
Excellent seedling selection and NPK fertilization can accelerate seedling, stem, leaf, and fruit growth. This study aimed to determine the effect of the number of seedlings and NPK-Phonska fertilizer on the growth and yield of lowland rice based on the leaf-color chart approach. This study was conducted from December 2021 to April 2022 in Puuroda Village, Baula, Kolaka. This study applied a randomized block experimental design with two-factor treatments, namely the number of seedlings and NPK-Phonska fertilizer dose. For the number of seedlings factor, there were one seedling per clump (B1), two seedlings per clump (B2), and three seedlings per clump (B3). The NPK-Phonska fertilizer factor contained two treatments, namely, without fertilizer treatment (M0) and fertilizer treatment based on the average dose of leaf-color chart (M1). The results of this study showed that two and three seedlings per clump had higher growth and yield of lowland rice, based on the plant height, maximum number of tillers, number of productive tillers, panicle length, dry grain yield (kg/plot), grain yield (ton/ha). The NPK fertilizer affects the growth and yield of lowland rice based on the leaf-color chart.